Rancang Bangun Aplikasi Pengelolahan Data Penempatan TKI Asal Timor Ke Luar Negeri Berbasis Web Studi Kasus (BP3TKI) Kupang - Aril Wabang, Yabes Vridman; A. Nani, Paskalis; A.N. Samane, Ign. Pricher (Jurnal Teknik Informatika UNIKA Santo Thomas, 2021)
The Indonesian Worker Placement and Protection Service Agency (BP3TKI) has the authority to provide services for people who wish to run for Indonesian Workers (TKI). In this case, of course the BP3TKI Office has a lot of important data that will be well managed so that its integrity is maintained. All important data will be processed in the Placement section of the BP3TKI Office. In managing TKI data, the placement section uses Microsoft Excel which is managed by one person and only uses one Personal Computer (PC) unit in the placement section. Because the data is managed by one person with one PC and is not stored in the database, it is very possible that the data that has been managed will be lost if one day the PC in the placement section is damaged, this will make it difficult for the placement employee to find data when required return. For this reason, a "WEB-BASED DESIGN OF DATA PROCESSING APPLICATION FOR PLACEMENT OF TKI ORDER OF TIMOR ABROAD BASED ON WEB-BASED" was made. The method used in this system is the Waterfall Model. This system is designed based on Web, using PHP programming language and database storage media using MySql. It is hoped that this system can manage and store TKI data properly and safely and facilitate the data search process.